Importance of fasting serum glucose, haemoglobin a1c and fructosamine in the diagnosis of diabetes - Bahadır Ersan; Mahmut Ok (Eurasian Journal of Veterinary Sciences)
Aim: The primary aim of this study was to evaluate the changes in hematological and certain biochemical parameters in the diagnosis of rabbits with experimental diabetes mellitus induced with two different doses of alloxan monohydrate (100 and 175 mg/kg). The secondary aim of this study was to determine the importance of glucose, haemoglobin A1c and fructosamine in the diagnosis of the disease. Materials and Methods: Rabbits were randomly allocated to two groups. The first group included 12 rabbits and the second group included 13 rabbits. Hundred and 175 mg/ kg dose of the alloxan solutions were given intravenously to the first group and second group, respectively. White blood cell, red blood cell, haemoglobin, platelet counts, paced cell volume, mean corpuscular haemoglobin concentration and mean corpuscular volume values were determined. Fasting serum glucose, fructosamine, insulin, haemoglobin HbA1c, total cholesterol, triglyceride, urea, aspartate amino transferase and alanin amino transferase levels were measured. Results: Statistically significantly increases of serum fasting glucose, fructosamine, haemoglobin A1c, total cholesterol and triglyceride concentrations and decreases of serum insulin levels and red blood cell, paced cell volume and haemoglobin values were determined (p<0.05) in both groups. Conclusion: Fasting serum glucose, fructosamine and haemoglobin A1c could be more important indicators for the diagnosis of diabetes mellitus.